Critical entrepreneurship education: a form of resistance to McEducation? - Hytti Ulla (Routledge, 2022)
This conceptual chapter discusses why some individuals resist the entry of entrepreneurship into the university, and how critical entrepreneurship education could be a solution for embedding entrepreneurship at the universities in a sustainable way.
Universities are increasingly expected to strengthen their role in society (Jarvis 2013). This also suggests a transition towards ‘entrepreneurial university’ (Etzkowitz 2014; Foss and Gibson 2015) and a reorientation of university strategies and policies to promoting entrepreneurship and societal impact (Siegel & Wright 2015). One tenet in this development is increasing the supply of entrepreneurship education and training modules campus-wide. This strong wind of entrepreneurship into the universities is not without critics. The resisting voices are asking will the move towards the entrepreneurial university erase any attempts to safeguard the traditional values and threaten the academic ethos of the Humboldtian university (Philpott et al., 2011).
In the chapter I argue that the academics are not resisting the entry of entrepreneurship into the university per se but they are resisting the ways it is introduced and the ways entrepreneurship is understood. The resistance is targeted at the narrow interpretation of entrepreneurship, and to the implementation of entrepreneurship as a managerial, top-down project (Philpott et al, 2011; Kolhinen, 2015), and at understanding university as a place of educational consumption and students as consumers. This is discussed through the metaphor of McDonaldisation of higher education (Ritzer, 1998), that I find insightful for thinking about entrepreneurship education in universities.
In this McEducation version of entrepreneurship education the university takes a one-size-fits-all approach by claiming that once entrepreneurship courses and services are offered campus-wide and are open to all, they are available to all. Yet, this has been questioned (Komulainen et al. 2009) Inclusion cannot be achieved simply by increasing numbers, and thus inclusion does not in itself bring greater equality (Delanty, 2003). The strong new venture creation focus combined often with a technology or science bias in reality means that the entrepreneurship becomes an elitist and narrow approach and the vast majority of students for example in humanities and social sciences become excluded from them. This one-size fits all model is oblivious to the questions of gender (Berglund et al. 2017). Importantly, all axiological debates in entrepreneurship education are silenced, marked by the lack of ‘why’ questions (Kyrö, 2015).
I advocate that the success of the entrepreneurship agenda is strongly dependent on whether or not the university relies on its core Humboldtian values of criticality and reflexivity in introducing entrepreneurship into the university. Thus, my take on entrepreneurship education will not emphasise the choice between the traditional academic and entrepreneurial values. Rather, I wish to join Fayolle (2013) and Kyrö (2015) and proponents of critical entrepreneurship education in the forthcoming book in their call for more reflective approaches and reflexivity as a necessary condition in furthering entrepreneurship education. The McDonaldisation of education is not a guarantee of success for embedding entrepreneurship at the university, on the contrary, it has the risk of becoming a functionalist pervasive ideology that may be taken to mean anything to anyone, and it easily and often becomes a contested concept (Alvesson and Spicer, 2012).
Revitilizing Entrepreneurship Education: Adopting a Critical Adopting a Critical Approach in the Classroom